Clonidine as an Additive to Local Anesthetics in Caudal Block for Postoperative Analgesia in Pediatric Surgery: A Systematic Review and Meta-Analysis - Wang, Ye; Guo, Qianqian; An, Qi; Zhao, Lin; Wu, Meng; Guo, Zhenggang; Zhang, Changsheng (Frontiers in Medicine, 2021)
Background: Clonidine is an anesthetic with favorable efficacy and safety profiles for caudal epidural block, but comparisons with other adjuvants need to be confirmed in pediatric patients. Aim: To investigate the effects of clonidine as an adjuvant in caudal epidural block to improve the intraoperative and postoperative analgesia in pediatric surgery. Methods: PubMed, Embase, and the Cochrane Library were searched for available papers published up to February 2021. The outcomes were pain score, duration of analgesia, complications, and number of analgesic requirements. The meta-analysis was performed using random-effects models. Results: Fifteen randomized controlled trials (RCTs) were included. There were no differences between clonidine and the control drug regarding the duration of analgesia (SMD=-0.71, 95%CI: -1.64, 0.23; I2=95.5%, Pheterogeneity<0.001), pain score (SMD=0.35, 95%CI: -0.28, 0.98; I2=80.8%, Pheterogeneity<0.001), and requirement for additional analgesia (OR=8.77, 95%CI: 0.70, 110.58, I2=81.9%, Pheterogeneity=0.004), but using clonidine resulted in fewer complications than the control drugs (OR=0.33, 95%CI: 0.20, 0.54, I2=21.8%, Pheterogeneity=0.217). The sensitivity analysis showed that the results were robust. A publication bias was observed. Conclusion: Clonidine has the same efficacy as the control drugs for caudal epidural block for pediatric surgery but fewer complications. These results support clonidine as an adjuvant to local anesthetic, but additional studies should be conducted.